Advances in Traditional Chinese Medicine for the treatment of hyperuricemia and associated diseases: pathogenesis, mechanisms, and future directions - Huang, Zhuo; Li, Bushuang; Bi, Ming-hui (Frontiers in Nutrition, 2025)
Hyperuricemia (HUA), characterized by elevated serum uric acid levels (>420 μmol/L), is a metabolic disorder linked to gout, cardiovascular diseases, renal disorders, diabetes, polycystic ovary syndrome (PCOS), and non-alcoholic fatty liver disease (NAFLD). Traditional Chinese Medicine (TCM) offers a holistic approach to HUA management, employing dialectical treatments to address underlying pathogenesis, reduce uric acid, mitigate inflammation, and protect organ function. This review synthesizes recent advances in TCM for HUA and its comorbidities, drawing from pharmacological studies of single herbs, compound formulas, and TCM pathogenesis theories. We introduce innovative strategies, including network pharmacology, metabolomics, personalized TCM diagnostics, and nanotechnology, to enhance therapeutic precision and efficacy. By integrating TCM's traditional wisdom—emphasizing balance among vital energies like “qi” (vital energy) and bodily fluids, with modern scientific methodologies, this review highlights potential risks, toxicities, and challenges in TCM application, aiming to improve patient outcomes in HUA and related diseases.